Monocarboxylate Transporter 1 May Benefit Cerebral Ischemia via Facilitating Lactate Transport From Glial Cells to Neurons - Zhang, Mao; Wang, Yanyan; Bai, Yun; Dai, Limeng; Guo, Hong (Frontiers in Neurology, 2022)
Monocarboxylate transporter 1 (MCT1) is expressed in glial cells and some populations of neurons. MCT1 facilitates astrocytes or oligodendrocytes (OLs) in energy supplement of neurons, which is crucial for maintaining neuronal activity and axonal function. It is suggested that MCT1 upregulation in cerebral ischemia is protective to ischemia/reperfusion (I/R) injury. Otherwise, its underlying mechanism hasn’t been clearly discussed. In this review, it provides a novel insight that MCT1 may protect brain from I/R injury via facilitating lactate transport from glial cells (including astrocytes and OLs) to neurons. It extensively discusses (1) the structure and localization of MCT1; (2) the regulation of MCT1 in lactate transport among astrocytes, OLs and neurons; (3) the regulation of MCT1 in cellular response of lactate accumulation under ischemic attack. At last, this review concludes that MCT1, in cerebral ischemia, may improve lactate transport from glial cells to neurons, which subsequently alleviates cellular damage induced by lactate accumulation (mostly in glial cells), and meets energy metabolism of neurons.